2021
DOI: 10.1515/spp-2021-0017
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Consequences of Income Inequality – An Overview

Abstract: Rising income inequality is one of the greatest challenges facing advanced economies today. Income inequality is multifaceted and is not the inevitable outcome of irresistible structural forces such as globalisation or technological development. Instead, this review shows that inequality has largely been driven by a multitude of political choices. The embrace of neoliberalism since the 1980s has provided the key catalyst for political and policy changes in the realms of union regulation, executive pay, the wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Income inequality is one of the greatest challenges facing the world's advanced economies today (Polacko, 2021). It has been cited as the “primary issue in terms of economic and social sustainability” (Lee, 2009, p. 4).…”
Section: Income Inequalitymentioning
confidence: 99%
“…Income inequality is one of the greatest challenges facing the world's advanced economies today (Polacko, 2021). It has been cited as the “primary issue in terms of economic and social sustainability” (Lee, 2009, p. 4).…”
Section: Income Inequalitymentioning
confidence: 99%
“…Inequality in the distribution of income has been present in the U.S. since early in the 20 th century when it was reported that approximately 15%-18% of the nation"s income went to the richest top 1 percent (see King, 1915;Piketty and Saez, 2003). Rising inequality in the distribution of income, which the U.S. has witnessed since the late 1970s (Hoffmann et al 2020;Clemens, 2022), tends to have an adverse impact on economic development and other economic and social outcomes (Galor and Zeira, 1993;Neckerman and Torche, 2007;Stiglitz, 2012 and2015;and Corak, 2013;Polacko, 2021). Several studies have concluded that a significant effect from a rise in income inequality is through a downward pressure on demand growth (Bivens, 2017;Bivens, and Banerjee, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One study found lack of employment to be one of the primary sources of anomie among males in the United States and cited the association between one's work and their contribution to society to be a possible explanation [40]. A recent study concluded that increased income inequality had health and social consequences including chronic stress, depression, and shame and that these occurred mostly in low-income individuals [41]. Previous studies have also found that social isolation results from a lack of opportunity, lack of resources, and high levels of inequality, all of which act as barriers to social integration [9,28,41].…”
Section: Sociologymentioning
confidence: 99%
“…A recent study concluded that increased income inequality had health and social consequences including chronic stress, depression, and shame and that these occurred mostly in low-income individuals [41]. Previous studies have also found that social isolation results from a lack of opportunity, lack of resources, and high levels of inequality, all of which act as barriers to social integration [9,28,41]. In summary, through employment, providing for oneself and one's family, and upward social mobility, one is adhering to the socially constructed goal of self-reliance, and is integrated into their society.…”
Section: Sociologymentioning
confidence: 99%